Evaluasi media e-learning dengan tema mengkafani Jenazah di MA Al-Huda Bengkalis - Nopita, Rini; Vebrianto, Rian (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2025)
Educational media is one of the most important components of the teaching and learning process. The researchers at MA AL-Huda Bengkalis therefore want to develop e-learning resources based on the Sholat Jenazah topic. Using the Research and Development (R&D) technique, 22 teachers and 30 students from class X took part in the study. The researchers directly gathered data through the use of questionnaires and observational techniques. The researchers explained the objectives and purpose of the instruments to the respondents before distributing the questionnaires for them to fill out. Respondents were asked to review the quality of the educational materials utilized and answer questions via the Google Form platform. The gathered data was examined using descriptive analysis.The average score for 30 students on the learning media components was 4.33 with a standard deviation of 0.2, which is also categorized as Strongly Agree, according to the research findings. The average score for 22 teachers was 4.6 with a standard deviation of 0.12. Consequently, it can be claimed that e-learning resources are of exceptionally high caliber, suitable for the current digital age, and built on cutting-edge technology to support interactive learning exercises.